Emerging Trends and Technological Challenges in Avionics Systems: A Comprehensive Review - Gaco, Ma. Barbara; Geli, Martell Gerard Anthony (International Journal of Multidisciplinary Approach Research and Science, 2025)
Avionics is quickly shifting from independent subsystems to completely integrated systems intended to leverage technology to raise safety, effectiveness and sustainability in aviation. This paper provides a broad, but intensive, examination of the emerging trends and technological challenges that mark avionics a modern era. Using recent literature from Scopus, Web of Science, IEEE Xplore, ScienceDirect and other venues, it brings together themes around communications, navigation and surveillance technologies; integration of unmanned aircraft, artificial intelligence and machine learning; digital transformation; sustainability; human factors; reliability; and advanced manufacturing. Additionally, it highlights how these technologies interact with other themes with relevance to avionics including cognitive radio, digital twins, and predictive analytics amid pressing challenges surrounding spectrum, increasing complexity of systems, certification, and cybersecurity. Instead of separating these themes, the paper highlights how they work together and must be considered as a whole to advance technology, operations, and human factors. Together, the synthesized themes construct a methodical synthesis of beacons across domains for new generation researchers, engineers and regulators in advanced avionics.